Linearity and tone in the unfolding of information. Issue 2 (3rd July 2019) - O'Grady, Gerard; Bartlett, Tom
ABSTRACT: In this article, we show how speakers manage information flow in real time and signal their interactional expectations. Speech unfolds temporally, not only as a series of lexical items which are grouped into grammatical units, but also as a sequence of tone groups which have the potential to achieve an act of telling. While there is a general belief that speakers commence their discourse with information that is shared prior to telling information that updates the common ground, our analysis of a corpus of monologue and dialogue shows that matters are not so simple. Speakers' informational needs are balanced moment by moment within and between increments which are themselves shaped by the interlocutors' shifting apprehensions of communicative purpose and the extent of presumed shared information. In our analysis we combine (i) a speech functional analysis, (ii) a description of a hierarchy of informational foci and (iii) prosody in order to develop a detailed description of how speakers manage information flow in real time. This enables us to show how speakers simultaneously balance informational flow while signalling their interactional expectations. Our conclusion is that speakers manage information flow by balancing textual, interpersonal and ideational choices.